EXACT CONTROLLABILITY IN VISCOELASTICITY OF FADING MEMORY TYPE - Leugering, Günter (Applicable Analysis, 1984)
Distributed load control of motions governed by an abstract partial integrodifferential equation is studied. First a new system-theoretic approach to a mild solution theory of equations arising in viscoelasticity of fading memory type is developed. Then it is shown that control results for the damped abstract wave equation devolve to a special class of “virgin” material with fading memory.
Keywords: 93B05; 45K05; 73K05